2012
DOI: 10.1007/s10552-012-9961-6
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional analysis of the association between diet and insulin-like growth factor (IGF)-I, IGF-II, IGF-binding protein (IGFBP)-2, and IGFBP-3 in men in the United Kingdom

Abstract: Diet is associated with IGF-I and IGFBP-2 levels in men in the UK, and these peptides warrant further investigation as part of randomized trials of dietary interventions to reduce the risk or progression of prostate cancer. There is no evidence that IGF-II or IGFBP-3 are mediators of dietary associations with prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 35 publications
4
26
2
Order By: Relevance
“…Others have also reported similar associations between total protein intake and circulating IGF-I in men, women, and children [3,4,[13][14][15][16][17][18]. Similarly, others have shown positive associations between dairy protein [3,4,14], milk [13,18], and dairy products [3,18] intakes and circulating IGF-I concentrations [19].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Others have also reported similar associations between total protein intake and circulating IGF-I in men, women, and children [3,4,[13][14][15][16][17][18]. Similarly, others have shown positive associations between dairy protein [3,4,14], milk [13,18], and dairy products [3,18] intakes and circulating IGF-I concentrations [19].…”
Section: Discussionmentioning
confidence: 77%
“…Higher circulating concentrations of IGF-I are associated with an increased risk of breast cancer [2]. In well-nourished populations higher total protein and dairy protein intakes have been associated with higher circulating IGF-I concentrations [3,4]. Some [2,5], but not all [6], investigators have reported a modest positive association between adult height and circulating IGF-I concentrations, and others have found an inverted-U-shaped association between body mass index (BMI) and circulating IGF-I concentrations, with a peak occurring around 23 to 27 kg/m 2 , and those with low or high BMIs having relatively low circulating IGF-I concentrations [2,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies examined the association between milk/dairy protein intake and IGF-II levels; a large study of milk intake in elderly Japanese men ( p  = 0.001) [47] and a smaller study of dairy protein intake in Caucasian men (p = 0.28) [48]. The studies showed a very weak positive association between milk and dairy protein intake and IGF-II levels (effect estimate: <0.05 SDs, range 0.00–0.05 SDs, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The European Prospective Investigation into Cancer and Nutrition clearly confirmed the correlation between increased dairy protein consumption and raised IGF-1 serum concentrations in adults [129,130]. A recent cross-sectional analysis using data of 1,798 men in the UK demonstrated that for one standard deviation increase in dairy protein intake, IGF-1 increased by 6.02 ng/ml [131]. Among other animal- and plant-derived proteins, dairy protein was most strongly associated with increased IGF-1 serum concentrations [131].…”
Section: Introductionmentioning
confidence: 94%
“…A recent cross-sectional analysis using data of 1,798 men in the UK demonstrated that for one standard deviation increase in dairy protein intake, IGF-1 increased by 6.02 ng/ml [131]. Among other animal- and plant-derived proteins, dairy protein was most strongly associated with increased IGF-1 serum concentrations [131]. Notably, low versus high meat intake was not associated with a change of IGF-1 serum levels [131].…”
Section: Introductionmentioning
confidence: 99%